PENGARUH BABY MASSAGE TERHADAP PERKEMBANGAN BAYI - Sara Herlina; Siti Qomariah; Wiwi Sartika (LPPM Universitas Abdurrab, 2023)
Infancy is also called the golden age or golden age as well as a critical period for the development of a baby at the age of 0-12 months. According to national data, according to the Indonesian Ministry of Health, in 2014, 13% - 18% of children under five in Indonesia experienced growth and development disorders. Developmental problems in babies can be done with stimulation, one form of stimulation that is commonly done by parents for babies is tactile stimulation in the form of baby massage. This study aims to determine the effect of baby massage on infant development. This study used a pre-experimental research design with a one group pretest and posttest research approach. The sampling technique used was purposive sampling. The sample in this study were 23 infants aged 0-12 months. The data analysis used was univariate and bivariate using the Wilcoxon pretest-posttest. The results of data analysis obtained a p-value of 0.014 (p <0.05) which indicates that Ha is accepted and Ho is rejected. Thus it can be concluded that there is an influence between baby massage on baby development in the Simpang Baru Health Center work area. It is recommended for mothers who have babies to be able to massage the baby as often as possible because the mother's touch can improve the baby's development.